PARODI DAN KONTRAK SOSIAL: Performativitas Identitas dalam Media - Qoriatul Mahfudloh (LP3M IAI Al-Qolam Malang, 2019)
The media openness as part of technological expansion gives many opportunities for self-revealing. These openness constitute consequences towards society digitalization. The openness uttered several variations and forms of self identification for public. Although these openness urged towards new idea of freedom, it does not mean it flew without norms. Its normative freedom did not offer any way except the old prevailed within new current. One of these perfomativity also conducted in humor field, especially in this study of parody. When humor assumed as alternative way to alleviate the system responsibility which is overly normative in some ways, humor also had particularly social contract that should be bring to heel by all the performers. This study is expected to reveal some things as well as the queer identity represent themselves in the humor field. It also conducted to reveal how new rules/norms obtain to both rein and freed the space of particular identity.